Extracellular localization of pokeweed antiviral protein. - Ready, M P (1986)
Pokeweed antiviral protein is an enzyme of Mr 29,000 known to inactivate a wide variety of eukaryotic ribosomes. We have used electron microscopy to show that the antibody specific for the protein is bound within the cell wall matrix of leaf mesophyll cells from Phytolacca americana. Any penetration or breakage of the cell wall and membrane could allow the enzyme to enter the cytoplasm, where it is likely to inhibit protein synthesis in the damaged cell. We speculate that pokeweed antiviral protein is a defensive agent whose principal function is probably antiviral.